Between the arch and the basket: Queer notes on heterocentric indigenous people in museums and Museology - Baptista, Jean (Edições Universitárias Lusófonas, 2021)
This paper is dedicated to presenting four notes taken from my field and research notebooks on the relationship between museums, museology and indigenous sexualities dissenting from the western heterosexual matrix. Above all, it seeks to promote a theoretical relationship between LGBT Museology and Indigenous Museology, as well as other ways of thinking about museums related to indigenous peoples. The first note deals with the anti-object of the heterocentered indigenous, that is, the way of understanding the original peoples without sexual dissent from the heterosexual matrix of the West; the second presents the historical contributions about the invention of indigenous sexual dissidences, discussing from colonial records about the ruptures imposed on indigenous societies with regard to the colonization of their sexualities; the third presents the solid basis of the theoretical field of Sociomuseolgia where it would be possible to think of an Indigenous Museology from its intersection with the LGBT Museology; finally, it analyzes some of the main experiences of indigenous outings carried out in the Peruvian Travesti Museum, in the Americans GLBT Historical Society and Field Museum and in the headquarters of the SOMOSGay group, in Paraguay, indicating, with this, cases where the relationship between sexual dissidents, indigenous peoples and Museology were problematized in an efficient or promising way. At the same time, I question the power and possible paths of an LGBT Museology intersected with an Indigenous Museology. This relationship is justified by the need to overcome the violent colonial inheritances that the process of inventing indigenous sexual dissidences has left today. Keywords: Indigenous people; Museology; LGBT; Queer Theory